Prosumer Data Gathering and Grid State Forecast Using Smart Grid Technology - Bagus Satrio Utomo; Arif Bramantyo, Hutama; Dwi Wibisono, Randi; Adi Nugraha, Rizky (Knowledge on Sustainability, Longevity, and Interdisciplinary, 2025)
The increasing global energy demand, combined with environmental concerns, has accelerated the development of smart grids as a sustainable solution. Smart grids enable bidirectional energy and information flow, allowing users to also act as energy producers—referred to as "prosumers." Managing the complex dynamics of energy consumption and production among prosumers requires advanced data management and optimization strategies. This study reviews the latest techniques in energy data management and optimization within smart grids. It also proposes a framework for an Energy Management System (EMS) that integrates forecasting, data analytics, and decision-making processes to optimize energy distribution and enhance grid efficiency.